2023
DOI: 10.3390/ijerph20043104
|View full text |Cite
|
Sign up to set email alerts
|

Dating Violence among Undergraduate Medical Students at a Public University in Mexico City: An Exploratory Study

Abstract: Gender-based violence (GBV) and cyber-aggression are growing problems in Mexico, but there is a dearth of information on their associated risks. We aimed to determine the prevalence of dating violence (DV) and cyber-aggression in a public campus and compared students’ acceptability of abusive DV based on their sex and sexual orientation. We employed a cross-sectional design to survey 964 first-year medical students attending a public university. We analyzed who found “acceptable” abusive behaviors from a datin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
1
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
0
1
3
Order By: Relevance
“…In the literature, there are many studies showing differences between gender and exposure to dating violence (7)(8)(9)(10)21). In our study, no significant relationship was found between gender and exposure to dating violence.…”
Section: Discussioncontrasting
confidence: 69%
“…In the literature, there are many studies showing differences between gender and exposure to dating violence (7)(8)(9)(10)21). In our study, no significant relationship was found between gender and exposure to dating violence.…”
Section: Discussioncontrasting
confidence: 69%
“…Kişisel Bilgi Formu: Araştırmacılar tarafından ilgili literatür taranarak (8,10,11) oluşturulan form öğrencilerin sosyo-demografik bilgileri ve romantik ilişkilerin sorgulandığı 13 sorudan oluşmaktadır.…”
Section: Veri Toplama Araçlarıunclassified
“…Ölçeğin doğrudan saldırganlık ve izleme kontrol davranışı olmak üzere iki alt boyutu bulunmaktadır. Doğrudan saldırganlık boyutunda 11 madde (2,3,4,6,8,9,10,12,15,16,18. sorular), izleme kontrol boyutunda 9 madde (1,5,7,11,13,14,17,19,20.…”
Section: Veri Toplama Araçlarıunclassified
See 1 more Smart Citation